Altered expression of anti-apoptotic proteins in non-involved tissue from cancer-containing breasts. - Batchelder, A; Gordon-Weeks, A; Walker, R (2009)
In a previous investigation reduced apoptosis was identified in normal breast tissue from cancer-containing breasts away from the cancer in comparison to age-matched normal breast from women without cancer. The hypothesis for this study was that defects in expression of apoptotic regulatory and DNA repair proteins would facilitate persistence of genetic alterations and predispose to breast cancer development. Using immunohistochemistry normal breast from 120 age-matched women (58 with breast cancer, 62 without) was analysed for proliferation, apoptosis, bcl2, BAX, caspase 3, Hsp27, Hsp70, BRCA1, ATM and BARD1. All assessments were performed without knowledge as to whether it was a cancer case or control. A significant difference was found for apoptotic index which was higher in controls (P < 0.02). There was no change in apoptotic and proliferation index with age for cancer cases unlike controls. Higher expression of bcl2 (P = 0.001) and Hsp27 (P = 0.001) was found in normal breast from cancer-containing breast in comparison to controls. There were no differences in the other proteins. Apoptosis has been found to be reduced in normal breast in a separate cohort of women with breast cancer, along with increased expression of the anti-apoptotic proteins bcl2 and Hsp27. These alterations in apoptotic regulation would enhance tumour development. Further studies are needed to examine the value of these proteins as risk markers.